Amazonian indigenous peoples are threatened by Brazil's Highway BR-319. (May 2020) - Ferrante, Lucas; Gomes, Mércio; Fearnside, Philip Martin
Highlights: Brazil's planned reopening of Highway BR-319 threatens Amazonian indigenous peoples. BR-319 and planned side roads would bring conflicts from the "arc of deforestation". Indigenous people affected by the road have not been consulted as required by ILO-169. Brazil plans to only consult 5 of 63 indigenous areas within 150 km of the road. Building the road without full consultation would open a dangerous precedent. Abstract: The Amazon rainforest in Brazil is under the greatest human pressure in its history. This pressure is increasing under the current presidential administration, with proposed retraction of environmental and humanitarian protections. Among these pressures are new hydroelectric dams, railways and highways. An infrastructure project with especially far-reaching consequences is the reopening of Highway BR-319 right through the heart of the Amazon Forest. The highway connects Manaus in central Amazonia to Porto Velho in the "arc of deforestation" on the southern edge of the forest. The highway crosses one of the most conserved parts of the Amazon with a large concentration of Indigenous Lands (" Terras Indígenas "). Although Brazil is a signatory to ILO Convention 169, which establishes the need for consultation with indigenous peoples and traditional communities, consultations have so far not been held. Here we argue for the need for consultation of all indigenous peoples within 150 km of any part of the highway, comprising 63 Indigenous lands and five other areas containing indigenous communities that are directly threatened by the project.